Perfluorohexane adsorption in BCR-704 Faujasite zeolite benchmark studies for the seventh industrial fluid properties simulation challenge. - Ross, Richard B.; Brennan, John K.; Frankel, Kevin A.; Moore, Jonathan D.; Moore, Joshua D.; Mountain, Raymond D.; Ahmad, Riaz; Thommes, Matthias; Shen, Vincent K.; Schultz, Nathan E.; Siderius, Daniel W.; Smith, Kenneth D. (Fluid Phase Equilibria, 2014)
The primary goal of the seventh industrial fluid properties simulation challenge was to test the ability of mol. simulation methods to predict the adsorption of org. adsorbates in zeolitic materials. The challenge focused, in particular, on the adsorption of perfluorohexane in the BCR-704 Faujasite zeolite. Entrants were challenged to predict the adsorption of perfluorohexane in the zeolite at 293 K and at relative pressures of 0.01, 0.05, 0.1, 0.2, 0.4, 0.6, and 0.8. The relative pressure (P/Po) is defined as that relative to the bulk satn. pressure predicted by the model at a given temp. (293 K in this case). The predictions were judged by comparison to a set of exptl. detd. values which are published here for the first time and were not disclosed prior to the challenge to the entrants.Addnl. benchmark exptl. studies, also described here-in, were carried out and provided to entrants in order to aid in the development of new force fields and simulation methods to be employed in the challenge. These studies included argon and nitrogen adsorption in the BCR-704 Faujasite zeolite. Elemental anal. of the BCR-704 Faujasite type zeolite was also available to entrants via the Institute of Ref. Materials and Measurement (IRMM) report EUR 21065 [1]. [on SciFinder(R)]
Keywords: BCR faujasite zeolite benchmark fluid property perfluorohexane adsorption simulation